THE CHALLENGES OF MULTICULTURALISM IN DAWAH: A SOCIOLOGICAL APPROACH: Tantangan Multikulturalisme dalam Dakwah: Pendekatan Sosiologis - Naamy, Nazar (Mudabbir: Jurnal Manajemen Dakwah, 2022)
This research attempts to identify the main challenges faced by preachers in multicultural environments, with a focus on how social, economic, political, and cultural factors influence the practice of dawah (Islamic preaching). The study also analyzes the role of technology and social media in disseminating dawah messages within the increasingly complex context of multiculturalism. The research methodology employs a qualitative approach involving literature review and descriptive-qualitative data analysis. The findings reveal that the primary challenge in multicultural dawah is a deep understanding of diverse cultures and values. Preachers need strong communication skills and sensitivity to differences to achieve effectiveness in delivering religious messages. Furthermore, the use of technology and social media can be valuable tools in overcoming multicultural barriers by creating more open and inclusive spaces for dialogue. This research contributes to a better understanding of how multiculturalism impacts dawah practices and highlights the importance of a sociological approach in comprehending the social dynamics related to religion and culture in multicultural societies. With a better understanding of these challenges, preachers can be more effective in spreading their religious messages in increasingly diverse environments.